USING OF NEGATIVE WOUND PRESSURE THERAPY (NPWT): A CASE SERIES OF WOUND DISRUPTION AS A COMPLICATION OF A CAESAREAN SECTION - Herman Yosef Limpat Wihastyoko; Ellenora Resti Mustikaningrat; Dorothea Respa Kusumaningrat; Gisella Sekar Wruhastanti; Yohana Joni (Universitas Airlangga, 2024)
Highlights: Surgical site infection during caesarean section can cause complications, thereby increasing maternal mortality and morbidity, especially in groups at risk. VAC therapy can stimulate granulation tissue formation so that primary wound junctions occur. VAC shows its ability to close wounds entirely within 3-4 weeks. Abstract: Introduction: Wound disruption following caesarean sections is a common issue that can increase maternal mortality and morbidity. Several factors have been identified, including maternal, procedural, and antibiotic factors. The re-suturing method, primer, and secondary suture often fail, causing recurrent and delayed healing. Case Illustration: CASE 1: A 26-year-old woman, 7 days post-caesarean section, presented with a wet wound and yellowish serous fluid. Three weeks later, wound dehiscence occurred despite re-debridement and re-suturing. Subsequent installation of VAC resulted in granulation tissue and re-epithelialization. CASE 2: A 32-year-old woman, 14 days post-caesarean section, complained of weakness and pus in the surgical wound. Upon examination, a red-yellowish fluid was found, indicating wound dehiscence. Re-debridement and VAC installation led to the formation of granulation tissue and re-epithelialization. Discussion: VAC is the new wound care technique that suctions or collects excess exudate that absorbent gauze cannot accommodate. In comparison, absorbent gauze is limited in its capacity to absorb the fluid that produced in wounds. An innovation where the use of VAC, which has a negative pressure function, can stimulate granulation tissue to form and can bind the edges of the wound so that it can close naturally. Conclusion: In instances of wound disruption following surgery, such as in the case of a caesarean section, it may be prudent to contemplate re-debridement followed by re-suturing. VAC presents itself as a viable alternative for managing wound dehiscence until the formation of granulation tissue.